Comparison of pruritus and sensory qualities induced by capsaicin, histamine and cowhage. (8th July 2019) - Hawro, T.; Lehmann, S.; Deuring, E.; Weller, K.; Altrichter, S.; Church, M.K.; Maurer, M.; Metz, M.
Abstract: Background: In skin diseases and experimental models of pruritus, pure itch is accompanied by additional sensations that are poorly characterized. Objectives: This study compared the sensory qualities evoked by different models of experimentally induced pruritus including skin prick testing (SPT) with histamine or capsaicin and application of cowhage spicules. SPT as a method of capsaicin application was validated for this purpose. Methods: Two pilot experiments were performed in eight healthy volunteers. First, a concentration of 8% capsaicin was identified as evoking a reproducible itch using SPT. Further, a list of the seven most frequently reported sensations was chosen after SPT with 10 mg/mL histamine, 8% capsaicin and application of 40–45 cowhage spicules. Finally, 31 subjects were challenged with the same itch‐inducers. Wheal and flare were measured at 10, 20, 40, 60 and 90 min, itch intensity every minute for 30 min, and the overall evaluation of sensory descriptors were recorded on a 100‐mm visual analogue scale once itching had subsided. Results: Skin prick testing with histamine and capsaicin resulted in flare reactions, which were 23% smaller for capsaicin ( P < 0.001). Histamine, capsaicin and cowhage‐induced pruritus, the duration of which was shorter for cowhage than for histamine (13.5 ± 1.4 vs. 8.8 ± 1.2 min, P = 0.005). Different mediators induced sensations of different intensities. Capsaicin produced less itch and physical urge to scratch than histamine ( P = 0.001) and cowhage ( P < 0.001). However, both capsaicin and cowhage induced more burning than histamine ( P = 0.002 and P = 0.04, respectively). Provocation with cowhage caused more intense sensations of pricking than histamine ( P = 0.033). Conclusion: This study shows that provocation with histamine, capsaicin and cowhage results in itch responses that are different in their duration, the profile of accompanying sensations, and the flare that comes with the itch.